Chino : Anti-Chinese Racism in Mexico, 1880-1940 - Chang, Jason Oliver (Asian American experience., 2017)
From the late 19th century to the 1930s, antichinismo - the politics of racism against Chinese Mexicans - found potent expression in Mexico. Jason Oliver Chang delves into the untold story of how antichinismo helped the revolutionary Mexican state, and the elite in control, of it build their nation. As Chang shows, anti-Chinese politics shared intimate bonds with a romantic ideology that surrounded the transformation of the mass Indigenous peasantry into dignified mestizos.